Integration of Immunology in a Systems-Based Osteopathic Medical Curriculum - Zian Shabbir; Layla Mazdeyasnan; Naila Iqbal; Samuel Kadavakollu; Mahboob Qureshi; Reena Lamichhane-Khadka (International Medical Education)
Immunology is an important component of the medical curriculum. It provides a foundation for understanding the cellular and molecular processes by which the body protects itself from external substances and the immunological responses that contribute to the development of many illnesses. The inclusion of immunology in an osteopathic medical curriculum is essential to understanding the body’s defense systems as well as the alignment of osteopathic concepts with immunology. By encompassing innate and adaptive immunity, immunology reflects the interconnectedness of the body’s systems and the foundation for self-regulation inherent in osteopathy. A problem facing medical educators is determining how to facilitate students’ learning of immunological concepts in a way that will help them retain and apply the material throughout their clinical years and beyond. This paper aims to provide an immunology education framework designed to effectively integrate immunology topics across the preclinical courses of an osteopathic medical curriculum. Drawing insights from an extensive review of the literature and current medical curricula, we propose an integrative curriculum model that broadly incorporates fundamental concepts of immunology across multiple disciplines and systems-based courses horizontally as well as vertically over the preclinical years using clinical presentations and laboratory findings and further connecting them to osteopathic principles. This integrative curriculum will augment medical students’ understanding of immunology, making them better able to connect core concepts with clinical applications and enhance their application of immunological concepts in osteopathic patient care in alignment with the NBOME guidelines. Using the proposed integrative medical curriculum may better prepare medical students for providing holistic medical care and guidance to their future patients.